La représentation du moi vieillissant chez Annie Ernaux et Benoîte Groult - Kéri, Henriett (Verbum – Analecta Neolatina, 2015)
The ageing of the population is one of the greatest challenges for our society. It has been studied by different disciplines but research is quite rare in the domain of linguistics. This paper aims to give a stylistic analysis of how the ageing self is described by Annie Ernaux and Benoîte Groult in their autobiographical works. We are focusing on two aspects of the representation of the self: the designation and the description of the self. The first concentrates on the writers' use of personal pronouns through a subtle play with the names of the protagonist in Groult's autobiography, while the second briefly explores the figures of speech to describe the self in the works discussed.